Impact of ungulate exclusion on understorey succession in relation to forest management in the Intermountain Western United States. Issue 2 (1st November 2014) - Pekin, Burak K.; Endress, Bryan A.; Wisdom, Michael J.; Naylor, Bridgett J.; Parks, Catherine G.; Ewald, Jörg
Abstract Questions Do successional trajectories in plant diversity, heterogeneity and dominance respond differently to ungulate exclusion in unmanaged forests vs managed forests that are thinned and burned? Is vegetation in recently thinned and burned stands more sensitive to changes in the grazing regime? Location Northeast OR, USA. Methods We evaluated changes in plant community composition, diversity, heterogeneity and dominance under herbivory by multiple ungulates (cattle, elk, deer) vs ungulate exclusion at sites where trees were recently thinned and a prescribed burn was applied (managed), and in sites that were not thinned or burned in over 40 yr (unmanaged). Plant species diversity was calculated with the Simpsons index and richness as the total number of plant species. We estimated changes in plant community heterogeneity using a measure of taxonomic dissimilarity. Plant dominance was measured as the relative evenness among different plant functional groups (annual and perennial forbs and graminoids, and shrubs, subshrubs and trees). Results As expected, managed sites displayed more early succession species, such as annual forbs and annual graminoids, while unmanaged sites were dominated by late‐succession species such as shrubs, subshrubs and trees. Species richness, particularly of annuals, was strongly reduced when ungulates were excluded from managed sites, and to a lesser extent from unmanaged sites for some perennial plant species. Species diversity decreased to a slightly greater extent with ungulate exclusion at managed sites. Species dominance was not influenced by ungulate exclusion. The effect of ungulate exclusion on plant heterogeneity also depended on forest management. Heterogeneity increased at managed sites and decreased in unmanaged sites with ungulate exclusion. Overall, the change in vegetation composition over time increased with the exclusion of ungulates, particularly at managed sites. Conclusions The strength and direction of specific vegetation and diversity responses to ungulate exclusion vary with forest management, and the influence of ungulate exclusion on plant succession is more pronounced in recently thinned and burned sites. Management of wild and domestic ungulates thus needs to account for forest management activities that alter vegetation seral stage and increase the sensitivity of vegetation to the ungulate grazing regime.